Kajian Yuridis tentang Kebijakan Indonesia Dalam Memperkuat Hak Berdaulat Wilayah Zona Ekonomi Eksklusif Di Kepulauan Natuna - Muhammad Fanny Chamdani; Himuyatul Hasanah (Universitas Muhammadiyah Jember, 2020)
In this discussion the authors take a case study of the Natuna Islands because Indonesia is one of the countries threatened with loss because Chinese vessels violate the Exclusive Economic Zone (EEZ) in the Natuna Islands, Riau Islands Province which is part of Indonesia. At first glance, the gas-rich waters seem to enter China's sovereignty. China's claims to Indonesia's Exclusive Economic Zone have no legal basis and are not recognized by UNCLOS. So in this case an adequate set of legislation is needed in order to maintain and empower it. Reviewing various laws and regulations such as Laws, Government Regulations, Presidential Decrees, etc. relating to the handling of national borders and borders in the Natuna Islands region.